Phenotypic evaluation of fifteen glycine max (l.) merrill (vegetable soybean) varieties under mineral and bris soils of Malaysia - Abu Bakar, Siti Nurul Farhana; Phang, Ing Chia; Nordin, Mohd Shukor; Ibrahim, Maizatul Akma (Penerbit Universiti Teknologi Malaysia, 2015)
Glycine max (L.) Merrill (vegetable soybean) is an important vegetable mainly among the Asian community. It is mainly consumed by human as a highly nutritious and savory snack. Instead of having a relatively higher protein and lower oil contents, it is also has a sweet and better tasting. Thus, this study aims to investigate the phenotypic characteristics of fifteen varieties of Glycine max (L.) Merrill developed by the Asian Vegetable Research and Development Center (AVRDC), Taiwan in order to select the potential varieties to be planted under Malaysian environments. The fifteen varieties were planted under mineral and bris soils at International Islamic University Malaysia (IIUM) Kuantan, Pahang. Eight phenotypic traits included the seed numbers per plant, the pod numbers per plant, the weight of fifteen seeds per plant, the days to emergence per plant, the days to flowering per plant, the plants height per plant, the pods width per plant and the pods length per plant were measured. Selection of potential varieties were mainly done by determining the yielding characteristics. Among these eight morpho-agronomic characteristics, the seed numbers per plant is the main yield determinant while, the other characteristics would be useful for future breeding programs. From the observation, Variety 4 (AGS429) obtained the highest seed numbers per plant (81 seeds) under mineral soil and Variety 1 (AGS 190) produced the highest seed numbers per plant (91 seeds) under bris soil, thus having the promising higher yielding ability to be selected as a potential vegetable soybean varieties to be planted under Malaysian conditions.